Whole-Brain N-Acetylaspartate Concentration: Correlation with T2-Weighted Lesion Volume and Expanded Disability Status Scale Score in Cases of Relapsing-Remitting Multiple Sclerosis - Bonneville, Fabrice; Moriarty, David M.; Li, Belinda S.Y.; Babb, James S.; Grossman, Robert I.; Gonen, Oded (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: The T2-weighted MR imaging total lesion volume and Expanded Disability Status Scale (EDSS) score are two common measures of relapsing-remitting multiple sclerosis disability and pathologic abnormality. Because the whole-brain N-acetylaspartate concentration is considered to be a new marker of the disease burden, the purpose of this study was to evaluate the relationship among these three measures.METHODS: The whole-brain N-acetylaspartate concentration and T2-weighted lesion volume were quantified by using MR imaging and proton MR spectroscopy in 49 patients with relapsing-remitting multiple sclerosis (36 female and 13 male patients; average age, 39 years; age range, 24–55 years; average EDSS score, 2; range of EDSS scores, 0–6). Correlations among whole-brain N-acetylaspartate concentrations, T2-weighted lesion volumes, and EDSS scores were obtained.RESULTS: No correlation was found between whole-brain N-acetylaspartate levels and either T2-weighted lesion volumes or EDSS scores. A weak correlation was found between the EDSS scores and T2-weighted lesion volumes (P = .043, rs = 0.292).CONCLUSION: Despite the lack of correlation between whole-brain N-acetylaspartate concentration and the clinical disability reflected in the EDSS score, only the former evaluates the global neuronal cell disease in the entire brain, including those lesions that are occult to conventional imaging techniques.